Strategy for Increasing Community Participation in the Forest Waqf Program in Gunungkidul Regency - Sarno (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper analyzes the low level of community participation in the Forest Waqf Program in Gunungkidul Regency. The background of this study is the high rate of deforestation (forest destruction) and environmental damage in Indonesia, which prompted the Ministry of Religious Affairs (Kemenag) to develop an ecotheology program through a forest waqf initiative. Although Gunungkidul has been designated as a designated area for forest waqf management, community participation remains low, indicating a gap between the ideal potential of waqf as a conservation instrument and the reality of its implementation in the field. The specific problem that is the focus is the low level of literacy and public understanding of forest waqf, which is key to the urgency of the study to formulate appropriate policies. This study uses a descriptive qualitative methodology and policy analysis with instruments such as document review, limited interviews, and USG (Urgency, Seriousness, Growth) priority analysis. Theoretical frameworks such as the Theory of Islamic Financial Literacy, Diffusion of Innovation, and the Whole-of-Government (WoG) concept are used to analyze the root of the problem. The results and discussion indicate that low public literacy is identified as a top priority issue, with the root cause being the lack of innovative outreach and limited internal synergy within the Gunungkidul Ministry of Religious Affairs. An analysis of alternative policies using the William N. Dunn Criteria found that the policy of issuing a circular from the Regional Office Head concerning comprehensive guidelines for forest waqf socialization is the most effective and fundamental solution. The main conclusion is that the key to the success of forest waqf lies in improving internal communication governance and standardizing education. Therefore, it is recommended that the Head of the Yogyakarta Special Region Ministry of Religious Affairs Regional Office immediately issue the circular to ensure message consistency, method innovation, and the involvement of all parties at the Ministry of Religious Affairs in increasing literacy and community participation in the forest waqf program.